Thermodynamic factors of dicarba-closododecaboranes(12) configuraction stability - S. P. Knyazev; E. G. Gordeev; E. A. Chernyshov (Тонкие химические технологии, 2006)
Reactions of isomerisation 1,2-C2B10H12  1,7-C2B10H12 and 1,7-C2B10H12  1,12- C2B10H12 were analyzed at B3LYP/6-311G(2d,2p) level of theory. Thermodynamic parameters of these reactions were calculated at 298 – 1000 K. These parameters conform experimental data.